Predictors of Intention to Quit Waterpipe Smoking: A Survey of Arab Americans in Houston, Texas. (4th March 2015) - Athamneh, Liqa; Sansgiry, Sujit S.; Essien, E. James; Abughosh, Susan
Abstract : Waterpipe smoking has been described as "the second global tobacco epidemic since the cigarette." Both Middle Eastern ethnicity and having a friend of Middle Eastern ethnicity have been reported as significant predictors of waterpipe smoking. Addressing waterpipe smoking in this ethnic minority is essential to controlling this growing epidemic in the US. We investigated the predictors of an intention to quit waterpipe smoking by surveying 340 Arab American adults in the Houston area. Primary analyses were conducted using stepwise logistic regression. Only 27% of participants reported having an intention to quit waterpipe smoking. Intention to quit waterpipe smoking was significantly higher with history of cigar use, a prior attempt to quit, and not smoking when seriously ill and significantly lower with increasing age, medium cultural acceptability of using waterpipe among family, high cultural acceptability of using waterpipe among friends, longer duration of smoking sessions, and perceiving waterpipe smoking as less harmful than cigarettes. Educational programs that target Arab Americans in general, and specifically older adults, those who smoke waterpipe for more than 60 minutes, those whose family and friends approve waterpipe smoking, and those with no former attempts to quit, may be necessary to increase the intention to quit waterpipe smoking.